“Cinephemera” from a Librarianship Perspective: Theory, Practice, Cataloguing Evidence - Lucia Antonelli (Cinergie)
The article deals with cinephemera from a librarianship perspective through the analysis of theoreticalformal aspects and management practices in relation to catalogued records. In the context of library documentary categorizations cinephemera present elements of formal and substantial complexity; they can be considered as “non-book material”, gray literature, ephemera: typologies of documents for which the supporting role in cultural studies is increasingly recognized. The cinephemera theoretical and terminological complexities impact on their organization and their cataloguing activity and affect the sphere of relevance in archives and libraries too; as well as archives, many libraries manage non-textual and material resources useful for the reconstruction of spectatorial practices and film consumption. In this framework, the analysis focuses attention on the cataloguing evidence of cinephemera in a user-oriented perspective, questioning the possible effects theoretical and practical critical issues may have on the catalogues functionality and effectiveness. With this aim, the article presents the results of a survey conducted on cinephemera catalogued in the Opac SBN - postcards, press-book, posters, calendars and stickers produced in Italy between the 1930s and 1960s. Moreover, the analysis is accompanied by a specific study on press-book and posters of ENIC, a national cinematographic body which, from 1935 to 1956, carried out its activity in the movie distribution.